2021
DOI: 10.3390/molecules26226951
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Pressurized Liquid Extraction and In Vitro Neuroprotective Evaluation of Ammodaucus leucotrichus. Untargeted Metabolomics Analysis by UHPLC-MS/MS

Abstract: Ammodaucus leucotrichus is a spontaneous plant endemic of the North African region. An efficient selective pressurized liquid extraction (PLE) method was optimized to concentrate neuroprotective extracts from A. leucotrichus fruits. Green solvents were tested, namely ethanol and water, within a range of temperatures between 40 to 180 °C. Total carbohydrates and total phenolics were measured in extracts, as well as in vitro antioxidant capacity (DPPH radical scavenging), anticholinesterase (AChE) and anti-infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 49 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…According to the literature data (Abderrezag et al, 2021) reported that the mystical cumin seeds extracted using green solvents (ethanol and water) give a yield of phenolic compounds which found that the content of phenolic compounds in cumin was 5.38, 5.97 and 1.90 mg/g for methanolic, ethanolic and hexanic.…”
Section: Fl/pc -Fortification Factormentioning
confidence: 99%
“…According to the literature data (Abderrezag et al, 2021) reported that the mystical cumin seeds extracted using green solvents (ethanol and water) give a yield of phenolic compounds which found that the content of phenolic compounds in cumin was 5.38, 5.97 and 1.90 mg/g for methanolic, ethanolic and hexanic.…”
Section: Fl/pc -Fortification Factormentioning
confidence: 99%